Algal amendment enhances biogenic methane production from coals of different thermal maturity - Platt, George A.; Davis, Katherine J.; Schweitzer, Hannah D.; Smith, Heidi J.; Fields, Matthew W.; Barnhart, Elliott P.; Gerlach, Robin (Frontiers in Microbiology, 2023)
The addition of algal biomass to stimulate methane production in coal seams is a promising low carbon renewable coalbed methane enhancement technique. However, little is known about how the addition of algal biomass amendment affects methane production from coals of different thermal maturity. Here, we show that biogenic methane can be produced from five coals ranging in rank from lignite to low-volatile bituminous using a coal-derived microbial consortium in batch microcosms with and without algal amendment. The addition of 0.1 g/L algal biomass resulted in maximum methane production rates up to 37 days earlier and decreased the time required to reach maximum methane production by 17-19 days when compared to unamended, analogous microcosms. Cumulative methane production and methane production rate were generally highest in low rank, subbituminous coals, but no clear association between increasing vitrinite reflectance and decreasing methane production could be determined. Microbial community analysis revealed that archaeal populations were correlated with methane production rate (p=0.01), vitrinite reflectance (p=0.03), percent volatile matter (p=0.03), and fixed carbon (p=0.02), all of which are related to coal rank and composition. Sequences indicative of the acetoclastic methanogenic genus Methanosaeta dominated low rank coal microcosms. Amended treatments that had increased methane production relative to unamended analogs had high relative abundances of the hydrogenotrophic methanogenic genus Methanobacterium and the bacterial family Pseudomonadaceae. These results suggest that algal amendment may shift coal-derived microbial communities towards coal-degrading bacteria and CO2-reducing methanogens. These results have broad implications for understanding subsurface carbon cycling in coal beds and the adoption of low carbon renewable microbially enhanced coalbed methane techniques across a diverse range of coal geology.